Navigating the complexities of controller placement in SD-WANs: a multi-objective perspective on current trends and future challenges - Abdulghani, Abdulrahman M.; Abdullah, Azizol; Rahiman, A. R.; Abdul Hamid, Nor Asilah Wati; Akram, Bilal Omar; Raissouli, Hafsa (Tech Science Press, 2025)
This review article provides a comprehensive analysis of the latest advancements and persistent challenges in Software-Defined Wide Area Networks (SD-WANs), with a particular emphasis on the multi-objective Controller Placement Problem (CPP). As SD-WAN technology continues to gain prominence for its capacity to offer flexible and efficient network management, the task of 36optimally placing controllers—responsible for orchestrating and managing network traffic—remains a critical yet complex challenge. This review delves into recent innovations in multi-objective controller placement strategies, including clustering techniques, heuristic-based approaches, and the integration of machine learning and deep learning models. Each methodology is critically evaluated in terms of its ability to minimize network latency, enhance fault tolerance, and improve overall network performance. Furthermore, this paper discusses the inherent limitations and challenges associated with these techniques, providing a critical evaluation of their current utility and outlining potential avenues for future research. By offering a thorough overview of state-of-the-art approaches to multi-objective controller placement in SD-WANs, this review aims to inform ongoing advancements and highlight emerging research opportunities in this evolving field.